ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU TAS DI UD WIJAYA DENGAN METODE EOQ DAN EPQ - Nazilatus Sa'idah; Muhammad Zainuddin Fathoni; Hidayat Hidayat (LPPM Politeknik LP3I Medan, 2021)
Inventory systems have an important role to support business operations so as to achieve maximum profit. An inventory planning and control technique relates to the optimal amount of inventory that a company must have and also affects inventory costs. If the condition of the company has the right amount of inventory can make the company avoid shortages or excess supplies. Thus, inventory control is important in the ongoing business activities, one of which is in UD Wijaya. UD Wijaya as a micro, small and medium enterprise that has the production of bags with 2 types of fabric, namely CCI fabric and D300 fabric. The owner of the business always maintains the quality of raw materials used to maintain the smooth process of production. But the fact that the use of inventory control systems is still simple and minimal will be a good theory and based on estimates only. With these conditions there is often a buildup of raw materials in the market because the needs of raw materials are not adjusted to production needs so that the increase in expenditure costs will also increase. The purpose of the study was to determine the amount of inventory control using the EOQ and EPQ methods and determine the total minimum supply based on both methods. The results obtained showed that the EOQ and EPQ methods have almost the same amount of bag raw material inventory control, namely for CCI fabric types as much as 229 Roll and D300 fabric types as many as 170 Rolls. But in the EPQ method has the minimum total inventory cost. As for the total cost that must be incurred for the supply of raw materials of CCI fabric type amounting to Rp. 14,688,190 and for raw materials of D300 fabric type amounting to Rp. 10,040,780 So it is concluded that the Economic Production Quantity method can be used in the inventory control system in UD Wijaya.